Studi Penilaian Indikator Kinerja Das Konaweha Akibat Perubahan Tata Guna Lahan Berdasarkan Kriteria Hidrologis - Andono, Riwin; Limantara, Lily Montarcih; Juwono, Pitojo Tri (Fakultas Teknik, Universitas Brawijaya, 2014)
Watershed assessment using hydrology indicators is a quick and effective way to know the performance of the Konaweha watershed due to land use changes. Konaweha watershed is located in Sulawesi Tenggara Province, which includes Kendari City, Konawe, and Kolaka with its Â± 6020 km basin area. This study was conducted to evaluate the response of Konaweha watershed due to land use changes in the year of 2000 - 2010, and land use spatial direction (RTRW) of Sulawesi Tenggara Province, using spatial analysis methods by applying AVSWAT software. Watershed performance indicators which is used in the assessment indicators is discharge to know the value of Coefficient River Regim (KRS), runoff coefficient, and sediment transport in Konaweha Watershed. Based on both of the three indicators and the calculation of the spatial analysis showed that Konaweha Watershed is in good category. KRS values obtained in 2000 and 2010, as well as the spatial direction in between 99 - 102 indicating Konaweha watershed in medium category. Runoff coefficient indicator showed value in between 0.045 - 0.1 which indicating watershed in the good category. Furthermore, sediment transport indicators show the value of 0.5 - 0.105 were also indicating in good category. KRS values of Konaweha watershed which is in medium category, it is indicated that Konaweha watershed has poor capacity to retain and storage of water infiltration. Construction of dams, ponds, and other technical efforts are needed to be done in order to improve the performance of DAS Konaweha with decreasing the indicator score of River Regim Coefficient (KRS)Key words: Watershed Assesment, Land user changes, Hidrology